Dispensing Device to Deliver Small and Standardized Amount of Fluoride Dentifrice on the Toothbrush - Silvia José Chedid; Livia Maria Andaló Tenuta; Jaime Aparecido Cury (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the efficacy of a dispensing device specially developed to standardize the amount of fluoride dentifrice to be delivered on the toothbrush. The amount and variability of dentifrice applied using this device were compared with recommendations to apply dentifrice amounts equivalent to "rice size" or "pea-size". Material and Methods: Two dentifrices, one used by children (NaF/Silica-based) and one used by the entire family (MFP/CaCO3-based), and five methods to apply them on the toothbrush (pea and rice sizes, and three different amounts using the developed device) were tested by 12 volunteers. The amount of dentifrice placed on the toothbrush was weighed, and the experiment was repeated three times. Data were analyzed by two-way ANOVA and Tukey test. Results: No differences were observed between the dentifrices used (p>0.05), but the method of application significantly affected the amount  of  dentifrice applied (p<0.05). Smaller amounts (p<0.05) and less variability were observed when the volunteers used the dispenser device than when they were asked to apply a pea or rice size. Conclusion: The device can help parents and caregivers to safely use fluoride dentifrice on children.